2018
DOI: 10.1155/2018/6929732
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Progression of Mild Cognitive Impairment in Different Types of Neurodegenerative Disorders

Abstract: Objective Mild cognitive impairment (MCI) is a transitional state between normal aging and early dementia. It has a heterogeneous etiology and clinical course. This study aimed to examine the factors associated with the progression of MCI in different types of dementia disorders. Method A retrospective, longitudinal, observational study of outpatients with MCI was conducted at a medical center in northern Taiwan. Patient medical records were reviewed, and risk factors were analyzed by multivariate analysis. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 44 publications
1
27
1
4
Order By: Relevance
“…The mean number of chronic illnesses and the Charlson index were significantly higher in persons diagnosed with dementia compared to those with MCI or non-impaired individuals. A retrospective longitudinal study from Taiwan compared baseline clinical characteristics of 279 patients and compared those who remained to MCI and those who progressed to dementia (43). They identified significantly higher extent of dyslipidaemia in those with stable MCI and a borderline higher rate of depression in those who progressed to dementia.…”
Section: Co-morbidities In Participants With Dementia MCI and Non-imentioning
confidence: 99%
“…The mean number of chronic illnesses and the Charlson index were significantly higher in persons diagnosed with dementia compared to those with MCI or non-impaired individuals. A retrospective longitudinal study from Taiwan compared baseline clinical characteristics of 279 patients and compared those who remained to MCI and those who progressed to dementia (43). They identified significantly higher extent of dyslipidaemia in those with stable MCI and a borderline higher rate of depression in those who progressed to dementia.…”
Section: Co-morbidities In Participants With Dementia MCI and Non-imentioning
confidence: 99%
“…The prevalence of behavioural abnormalities associated with age-related cognitive decline is growing in older people [1]. Age is the most important risk factor for cognitive impairment and dementia because of natural changes like neuronal death or functional impairments [2].…”
Section: Introductionmentioning
confidence: 99%
“…convert to AD with a conversion rate of 13.7% per year (Huang, Wahlund, Svensson, Winblad, & Julin, 2002). A recent study, from different continents, also indicated high conversion of both amnesic (aMCI) as well as nonamnestic MCI (naMCI) to AD (Chen, Cheng, Lin, Lee, & Chou, 2018). Although the exact cause of AD is not yet known, recent studies have indicated that oxidative stress (OS) plays a profound role in AD pathogenesis (Mandal, Tripathi, & Sugunan, 2012;Markesbery, 1997;Saharan & Mandal, 2014).…”
mentioning
confidence: 99%